2012
DOI: 10.1136/tobaccocontrol-2012-050562
|View full text |Cite
|
Sign up to set email alerts
|

YouTube: a promotional vehicle for little cigars and cigarillos?

Abstract: The vast majority of information on YouTube about LCCs promotes their use. It is critical to monitor content on LCCs posted on YouTube, and develop appropriate health messages to counter pro-LCC content, and appropriately inform potential consumers of the harms associated with their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 22 publications
6
57
0
1
Order By: Relevance
“…Unlike other studies, most videos analysed had antismoking content. Nonetheless, in line with earlier studies,11 13 14 17 18 the pro-smoking videos had received more views and had a higher like:dislike ratio than the antismoking videos. As tobacco companies undertake more aggressive marketing in developing countries, pro-smoking videos appear to be a key medium with relatively high (and growing) reach among young people.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Unlike other studies, most videos analysed had antismoking content. Nonetheless, in line with earlier studies,11 13 14 17 18 the pro-smoking videos had received more views and had a higher like:dislike ratio than the antismoking videos. As tobacco companies undertake more aggressive marketing in developing countries, pro-smoking videos appear to be a key medium with relatively high (and growing) reach among young people.…”
Section: Discussionsupporting
confidence: 86%
“…Studies examining other tobacco products, such as smokeless tobacco and e-cigarettes, also found that YouTube videos are often pro-tobacco, and receive more ‘views’ than antitobacco videos 11 13 14 17 18…”
Section: Introductionmentioning
confidence: 99%
“…Our work builds on a growing body of the literature that uses mixed-method computational approaches to assess health trends from digital media24–26 38 39 54 and adds to prior literature by demonstrating that Twitter appears to be a major messaging and information-sharing social platform for LCCs. In fact, our study is first to quantify the overall presence of LCC-relevant content on Twitter.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Tobacco control researchers have also documented YouTube content related to other tobacco products popular with youth, such as hookah (Carroll, Shensa, & Primack, 2013), cigars and cigarillos (Richardson & Vallone, 2014), and smokeless tobacco or "dip" (Seidenberg, Rodgers, Rees, & Connolly, 2012). The videos featuring cigars and cigarillos had been viewed almost six million times at the time of the study, were most often viewed by males, and several of the videos were most often viewed by 13-17-year-olds.…”
Section: Tobaccomentioning
confidence: 99%